Penerapan Model Multivariat Analisis of Variance dalam Mengukur Persepsi Destinasi Wisata - Herman, Robert Tang (Binus Business Review, 2012)
The purpose of this research is to provide conceptual and infrastructure tools for Dinas Pariwisata DKI Jakarta to improve their capabilities for evaluating business performance based on market responsiveness. Capturing market responsiveness is the initial research to make industry mapping. Research steps started with secondary research to build data classification system. The second is primary research by collecting the data from market research. Data sources for secondary data were collected from Dinas Pariwisata DKI, while the primary data were collected from survey method using quetionaires addressed to the whole market. Then, analyze the data colleted with multivariate analysis of variance to develop the mapping. The result of cluster analysis distinguishes the potential market based on their responses to the industry classification, make the classification system, find the gaps and how important are they, and the another issue related to the role of the mapping system. So, this mapping system will help Dinas Pariwisata DKI to improve capabilities and the business performance based on the market responsiveness and, which is the potential market for each specific classification, know what their needs, wants and demand from that classification. This research contribution can be used to give the recommendation to Dinas Pariwisata DKI to deliver what market needs and wants to all the tourism place based on this classification resulting, to develop the market growth estimation; and for the long term is to improve the economic and market growth.